Development of HOTS-Based Learning Media Mikka (Komik Fisika) on Dynamic Fluid Materials - Darojatar Rofi'ah; Abdul Kholiq (IKIP Mataram, 2022)
Komik Fisika, hereinafter referred to as Mikka, is a learning medium in the form of comics with physics material by integrating High Order Thinking Skills (HOTS) skills. Research and development of this product is carried out with a waterfall design. This study aims to describe the feasibility of Mikka in terms of validity and effectiveness. The validity of the media is seen from the results of the validation instrument which is assessed by two validators with three aspects of assessment, namely learning aspects, material aspects, and media aspects. While the effectiveness of the media in terms of the questionnaire responses to research subjects, namely 22 students of class XI SMA Assa'adah Sampurnan Bungah Gresik and N-gain learning outcomes. The response questionnaire used consisted of usefulness, convenience, and satisfaction. Based on data analysis, it was found that Mikka's learning media had a validity percentage of 87.2% and was categorized as valid. In the aspect of effectiveness, Mikka is said to be very effective in being used in the learning process with an effectiveness percentage of 90.1% in terms of the response questionnaire and has a value of 0.35 qualified in terms of the calculation of the N-gain value. Thus, it can be concluded that Mikka's HOTS-based learning media on dynamic fluid materials is suitable for use in learning.